Fetal Assessment in Pregnancy (Indication and Methodology for Fetal Monitoring in a low-risk Population). Guideline of the DGGG, DEGUM, OEGGG and SGGG (S3-Level, AWMF Registry No. 015/089, February 2023) - Schiermeier, Sven; Von Kaisenberg, Constantin Sylvius; Kehl, Sven; Reister, Frank; Mosimann, Beatrice; Reif, Philipp; Harlfinger, Werner; König, Klaus; Schwarz, Christiane; Matern, Elke; Kühnert, Maritta; Schmitz, Ralf; et al. (Ultraschall in der Medizin, 2023)
Purpose ?The aim of this guideline was to find evidence on whether carrying out Doppler examinations and CTGs in low-risk cohorts of pregnant women improves outcomes. Methods ?First, a systematic search for guidelines was carried out. Identified guidelines were evaluated using the DELPHI instrument of the AWMF. Three guidelines were found to be suitable to evaluate CTG. Two DEGUM best practice guidelines were judged suitable to describe the methods. All studies on this issue were additionally analyzed using 8 PICO questions. A structured consensus of the participating professional societies was achieved using a nominal group process and a structured consensus conference moderated by an independent moderator. Recommendations ?No antepartum Doppler sonography examinations should be carried out in low-risk cohorts in the context of antenatal care. No antepartum CTG should be carried out in low-risk cohorts. Note ?The guideline will be published simultaneously in the official journals of both professional societies (i.?e., Geburtshilfe und Frauenheilkunde for the DGGG and Ultraschall in der Medizin/European Journal of Ultrasound for the DEGUM).
CRIS-Team Scopus Importer:2023-09-08
Keywords: check-up; CTG - cardiotocography; Doppler sonography; fetal assessment; guideline; pregnancy; prenatal care; ultrasound